HUBUNGAN PENDIDIKAN DENGAN KEMISKINAN DAN PENDAPATAN PERKAPITA SEBAGAI VARIABEL MEDIASI - Muliza Muliza (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Previous empirical studies that examined the relationship between education and poverty showed many contradictory results. Therefore, this study tries to include Per capita income as a mediating variable. The purpose of this study is to examine whether per capita income is able to mediate between education and poverty in Aceh Province. The data used in this study is secondary data with the period 2010-2021. To analyze the data, the method used is Path Analysis. The results showed that education was able to directly affect the poverty rate in the province of Aceh by 84.2%. Partially per capita income is able to mediate the relationship between education and poverty, this means it is important to improve the quality of the population by improving the quality of education, so that the population will be better able to increase income which will ultimately have an impact on reducing poverty.